PENGARUH PERSEPSI HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DI WAROENG STEAK & SHAKE JATIWARINGIN - Reynaldi Andryan; Darwin Raja Unggul Saragih (Human Capital Development, 2023)
This study aims to examine the effect of price perception, service quality, and location on purchasing decisions at Waroeng Steak and Shake Jatiwaringin. The research sample consisted of 100 respondents who were active customers of the restaurant. Data collected through questionnaires and analyzed with SPSS using multiple linear regression analysis method. The results of the study show that perceived price, service quality, and location significantly influence purchasing decisions at Waroeng Steak and Shake Jatiwaringin. Service quality also has a significant positive influence on consumer purchasing decisions.